(untitled) (Journal of Parents and Teachers, 2026)
The Society of Jesus seeks the holistic development of its students in order to bring about genuine transformation through the senses and the emotional realm. This article emphasises the idea that the true measure of educational success lies in the quality of life and service rather than in academic achievement.